SOME LEGAL ISSUES REGULATING THE RATIONAL USE OF AGRICULTURAL LAND IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2024)
The article was prepared within the framework of the grant project of the Ministry of Science and Higher Education of the Republic of Kazakhstan № AP14870596 «Problems of legal regulation of the rational use and protection of pasture ecosystems».Kazakhstan ranks sixth in the world in terms of pasture resources. As you know, more than 40 percent of the population lives in rural areas. Many of them would have nothing to spare if their own animals were neither their main income nor their living wage. However, the shortage of pastures has become a big problem for rural residents in recent years. In the 2021 Head of State Address, special attention was paid to this issue. At that time, Kassym-Zhomart Kemelovich paid special attention to the issues of providing pasture lands for personal subsidiary plots.The Address stipulates that, according to the Land Code, agricultural land will not be provided to foreigners, as well as priority provision of pasture for livestock in household plots of the population and an increase in the volume of land required for the procurement of feed, and is also instructed to ensure openness in the land sector and access to the land cadastral information and create a unified national database on the land fund and real estate.The Tax Code of the Republic of Kazakhstan does not provide benefits for enterprises processing agricultural products and agriculture. Processors purchase 90% of raw materials from peasant farms, and they are exempt from value added tax. At the same time, 50% of the price of finished products is the cost of raw materials. As a result, processing enterprises cannot credit value added tax that is subject to offset. All this today does not stimulate the competitiveness of enterprises processing agricultural products.One of the main problems of enterprises processing agricultural raw materials is the low competitiveness of domestic products. As you know, the basis of competition for any product is its quality and price. The high level of prices for the products of Kazakhstani processing enterprises is due to an increase in interest rates on bank loans, prices for transport services, as well as the current taxation system, especially the value added tax.The level of tax revenue from agriculture is low and it is focused only on agricultural processing. Compared to other industries, taxes from agriculture are minimal.Taxes are the main source of financing the political and economic activities of the state, since 90 percent of state budget revenues come from tax revenues. Today, in order for taxation and tax structure to help the whole world become competitive, it is necessary to stimulate efficiency and stability, and for this it is necessary to have a tax policy, to effectively, expediently implement tax regulation.Key words: pastures, taxes, agricultural products, land cadastre, undeveloped lands, value added tax, peasant farming.